Para além da escolha individual : um modelo de escolha social justificada - Ferreira, Carlos Roberto Bueno (2019)
The present thesis is an optimistic proposition of a social choice model that is able to maintain the formal power of logical analysis present on the mechanisms of choice without losing sight of the most basic philosophical arguments about just social life. It is the search for a solution that better fits the social reality in face of the apparent failure of the current mechanisms of election in contemporary democratic societies. For this, it is necessary to carefully evaluate the conditions of rationality, considering the system of requirements established in Social Choice Theory, searching for a viable answer that translates a true social choice and not just a sum of individual choices. In the meantime, it is necessary to evaluate the possibility of cooperation, given the individual concessions that must take place in a model of social choice. In the search for the translation of the individual will in intersubjective terms, to analyze and understand the reason that lead the individual to cooperate, becomes a fundamental question. A theory of the evolution of cooperation, helps us to understand what leads the individual to give up the purely selfish position without losing sight of the inherent rationality of individual choice. The solution that is presented is a two step procedure. The first step is to establish a cooperative equilibrium. The second is the maintenance and rebalancing of the established cooperation. For the second part of the procedure the model chosen is the discursive model of reciprocal justification as an alternative to print autonomous, cooperative and nonauthoritarian decisions. In this model there must be always open space for deliberation and a justified rationality that guarantees autonomy, not arbitrariness and that serves, analogously, as a main strategy to curb noncooperative action. Justification, in these terms, is considered not only as a right (Recht auf Rechtfertigung), but as a reciprocal duty, aiming to fill the information deficit in decision making. The approach of justified and reciprocal choice proposed here functions as a central planner who, with the statements of the agents themselves, is able to better evaluate the rationality that informs the social decision and may even foresee and detect any errors and anomalies, both in the selection process as in the results of the choice.